Principals’ Transformational Leadership and Its Role in Shaping Teachers’ Differentiated Instruction and Student Achievement: A Systematic Literature Review - Dede Wiwif Furqoni; Diding Nurdin; Nurdin Nurdin (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2026)
Abstract: This study aimed to examine how principals’ transformational leadership is positioned in the recent literature as a factor shaping teachers’ differentiated instruction and student achievement. Using a Systematic Literature Review (SLR) supported by bibliometric mapping, the study analyzed 27 Scopus-indexed publications published between 2021 and 2026. The dataset was retrieved through a structured search strategy using the keywords transformational leadership, principal or school leader, and differentiated learning or adaptive teaching, and was analyzed descriptively through Scopus indicators and VOSviewer keyword co-occurrence mapping. The findings show that differentiated instruction occupies the most central position in the literature, functioning as the conceptual link between leadership, teaching practice, learner diversity, and academic outcomes. The bibliometric results also reveal that the field remains concentrated in a limited number of authors, institutions, and countries, with Australia and the United States dominating publication output. Substantively, the reviewed studies indicate that principals’ transformational leadership influences student achievement mainly through indirect pathways, especially by improving teacher motivation, professional capacity, collaboration, and readiness to implement differentiated instruction. However, the relationship is not linear, as its effectiveness depends on contextual conditions such as teacher beliefs, assessment literacy, class composition, institutional support, and national policy environments. This study concludes that transformational leadership should be understood as a catalytic mechanism that strengthens teachers’ ability to deliver differentiated instruction in heterogeneous classrooms. It is therefore suggested that future research adopt more integrative and comparative designs, while policymakers and school leaders should prioritize professional development, formative assessment support, and collaborative cultures that enable differentiated instruction to be implemented more consistently and effectively. Keywords: differentiated instruction; school principals; student achievement; transformational leadership.